Sisi Gelap Dunia Islam Abad Pertengahan Menjelang Perang Salib Pertama (489-492 H/ 1096-1099 M): The Dark Side of the Medieval Islamic World on the Eve of the First Crusade (489-492 Ah / 1096-1099 Ce) - Mohd Bakri, Mohamad Fikri; Mohd Nor, Mohd Roslan; Gokaru, Shu’aibu Umar (Al-Basirah Journal, 2025)
This study examines critical aspects of medieval Islamic society from the 10th to the late 11th century CE that may have contributed to internal weaknesses prior to the arrival of the First Crusade (1095–1099 CE). Existing studies on the Crusades often focus on external factors, such as Pope Urban II’s call and the motivations of European Christians behind the fall of several Islamic cities in the Bilād al-Shām region, including Bayt al-Maqdis (Jerusalem). However, they pay less attention to the internal conditions of the Islamic world that may have facilitated the early success of the Crusader expedition. Through a historical analysis of medieval Arabic primary sources, this study explores internal conflicts, political fragmentation, socio-economic issues, and institutional decline that plagued the Islamic world at the time. Preliminary findings suggest that the schism between the Fatimid caliphate in Egypt and the ‘Abbasids in Baghdad, ongoing Sunni-Shi’a conflicts, power struggles among local dynasties such as the Seljuqs, and economic crises due to disruptions in trade routes weakened the Islamic world’s resilience. This study hopes to provide an alternative perspective on the internal factors contributing to the early success of the First Crusade while enriching the literature on medieval Islamic history with a critical focus that has long been overlooked.